2019
DOI: 10.1103/physrevaccelbeams.22.081301
|View full text |Cite
|
Sign up to set email alerts
|

Positron transport and acceleration in beam-driven plasma wakefield accelerators using plasma columns

Abstract: A finite radius plasma is proposed to generate wakefields that can focus and accelerate positron beams in a plasma wakefield accelerator. The finite radius plasma reduces the restoring force acting on the plasma electrons forming the plasma wakefield, resulting in an elongation of the on-axis return point of the electrons and, hence, creating a long, high-density electron filament. This results in a region with accelerating and focusing fields for positrons, allowing for the acceleration and quality-preserving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Besides energy transfer from head-to-tail using long positron beams [18], controlling the wakefield structure is the way to enable simultaneous focusing and acceleration for positrons. It is possible to achieve such advanced control by using shaped drivers [19,20] or plasmas [21][22][23]. For the latter, positron (and electron) acceleration in hollow channels is attractive because of its vanishing transverse focusing fields, which ensures emittance preservation, and enable even higher acceleration efficiencies compared to the nonlinear blowout regime [24][25][26][27].…”
mentioning
confidence: 99%
“…Besides energy transfer from head-to-tail using long positron beams [18], controlling the wakefield structure is the way to enable simultaneous focusing and acceleration for positrons. It is possible to achieve such advanced control by using shaped drivers [19,20] or plasmas [21][22][23]. For the latter, positron (and electron) acceleration in hollow channels is attractive because of its vanishing transverse focusing fields, which ensures emittance preservation, and enable even higher acceleration efficiencies compared to the nonlinear blowout regime [24][25][26][27].…”
mentioning
confidence: 99%
“…Using of plasma in transport channel can make it difficult to transport of the positron bunches. Positron witness bunch transport in PDWA may face the same problems that exist in PWFA studies (see [31][32][33] and references there). Although the first analytical studies have shown the possibility of focusing accelerated positron bunches in PDWA [23,34], a full numerical simulation, taking into account the self-consistent dynamics of the drive electron and accelerated positron bunches, taking into account the group velocity effects [35], have just begun.…”
Section: Introductionmentioning
confidence: 95%
“…Various methods have * weilu@tsinghua.edu.cn been proposed to address the plasma wakefield e + acceleration problem for a compact e + e − collider. A hollow laser [14] or electron beam [15] driver was proposed for e + acceleration in a uniform plasma, and a finite-width plasma driven by an e − bunch [16,17] was considered for e + acceleration and transport. Recently, multi-GeV acceleration of e + particles has been demonstrated in an e + self-loaded plasma wakefield [18].…”
Section: Introductionmentioning
confidence: 99%